Strategi Guru Dalam Mengatasi Kesulitan Membaca Pada Siswa Kelas IV SD Negeri 81 Kota Bengkulu - Pratama, Thaufiq Mieza; Muktadir, Abdul; Ariffiando, Nady Febri (JURIDIKDAS, 2024)
This study aims to describe the teacher strategies in overcoming reading difficulties not fourth grade students of SD Negeri 81 Bengkulu City. This study uses a descriptive methodology and is qualitative in nature. Teachers and students were the study's subjects, namely fourth grade teachers and fourth grade students of SD Negeri 81 Bengkulu City. Data collection techniques used observation, interviews, and documentation. Data analysis techniques were carried out by collecting data, reducing data, presenting data, and drawing conclusions. Data validity used triangulation techniques and extended observation. The results showed that the teacher's strategies to overcome reading difficulties in students of SD Negeri 81 Bengkulu City, are (1) identifying by providing reading (2) Individual approach by providing motivation and individual approach (3) Providing individual guidance by means of the alphabet method and additional hours (4) Cooperating with parents by calling students' parents to help solve problems (5) reading activity before and after learning. (6) Implementing cooperative strategies by reading with teachers and students (7) Utilizing the reading corner. Teacher has not used learning media in overcoming students' reading difficulties. Based on the results of the study, it can be concluded that teachers have guided students who have difficulty reading by carrying out seven activities except utilizing learning media.